Application of Delphi method and analytic hierarchy process to establish indicator system for evaluation of rational drug use in children with primary nephrotic syndrome: Observational study. Issue 19 (May 2020) - Lin, Mao; Zeng, Linan; Huang, Liang; Tao, Yuhong; Zhang, Lingli
Abstract : Abstract: Nephrotic syndrome (NS) can be divided into primary, secondary, and congenital NS 3 types, and primary nephrotic syndrome (PNS) accounts for about 90% of the total number of NS in children, which is a common childhood glomerular disease one. The treatment of children with PNS has been controversial and confused because of hormone tolerance, complications, multiple drug combinations, and other issues, but there are no indicators to assess the rational drug use (RDU) of children with PNS. This study aims to develop a set of indicators to assess the RDU in children with PNS. The study is an observational study and the procedure includes 3 steps: Systematic review: searched the websites, guidelines, and studies to establish the initial indicators. Expert consultation: applied the modified Delphi method among experts in the field of nephrology for a two-round collaborative consensus project. Obtained the final indicators by modifying each round based on the comments provided by the experts. Analytic Hierarchy Process: applied the AHP to determine the weight of each indicator. A consensus was reached after 2 rounds of the Delphi survey and each indicator was weighted. The final indicators included 2 first-rank indicators and 16 second-rank indicators. In round 1, modified 3 indicators, increase 2 indicators and delete 6 indicators. In round 2, reached consensus. The first-rank indicators comprised drug choice (46.96%) and drug usage and dosage (53.04%); The second-rank indicators aimed to the specific drug therapy, including the RDU of hormones, immunomodulators, and adjuvant drug. The score of each indicator met the requirements, therefore, childrens PNS RDU evaluation index system had been established and the index was scientific and credible. The first set indicators had been established to assess RDU of children with PNS. Monitoring these indicators will guide people towards the promotion of RDU for PNS. Whats more, the indicator provided a methodological reference for the development of other indicator sets.